2013
DOI: 10.1371/journal.pone.0054600
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Serum Concentrations of Lipopolysaccharide-Binding Protein (LBP) in the Adult Population: The Role of Obesity

Abstract: Background and AimAssessment of serum concentration of lipopolysaccharide (LPS)-binding protein (LBP) has been suggested as a useful biomarker to indicate activation of innate immune responses to microbial products. We investigated LBP concentrations and associations with demographics, lifestyle factors, and common metabolic abnormalities in adults. We also examined if LBP concentrations were associated with common polymorphisms in genes coding for LBP (rs2232618), CD14 (rs2569190), and TLR4 (rs4986790), the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
134
6
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(162 citation statements)
references
References 70 publications
20
134
6
2
Order By: Relevance
“…LBP recognises the lipid A component of LPS monomers and accelerates LPS binding to CD14, enhancing the sensitivity of cells to LPS [12,13]. Previous reports have shown a strong association between concentration of circulating LBP and obesity-associated metabolic disturbances [14][15][16][17]. In agreement with these studies, we found that concentrations of circulating LBP increased in obesity and decreased after weight loss [18].…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…LBP recognises the lipid A component of LPS monomers and accelerates LPS binding to CD14, enhancing the sensitivity of cells to LPS [12,13]. Previous reports have shown a strong association between concentration of circulating LBP and obesity-associated metabolic disturbances [14][15][16][17]. In agreement with these studies, we found that concentrations of circulating LBP increased in obesity and decreased after weight loss [18].…”
Section: Introductionsupporting
confidence: 90%
“…In agreement with these studies, we found that concentrations of circulating LBP increased in obesity and decreased after weight loss [18]. However, despite the association of LBP concentration with changes in fat mass, all these studies claimed the liver as the main source of variation in the concentration of circulating LBP [14][15][16][17][18]. A recent study described LBP secretion by 3T3-L1 adipocytes [19] and increased serum LBP levels in genetically and diet-induced obese mice after LPS injection, but AT LBP production was not investigated [19].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Chez l'homme, en situation de sepsis, une corrélation a été montrée entre les taux sériques de LPS et de LBP (LPS-binding protein) plasmatique, une protéine qui interagit avec le complexe récepteur aux lipopolysaccharides [14]. Des taux plus élevés de LBP ont été rapportés chez des sujets en surpoids et obèses [32][33][34]. Ils pourraient être liés à l'inflammation systémique de bas grade que l'on observe chez ces sujets.…”
Section: Perméabilité Intestinale Et Modifications Immuno-inflammatoiunclassified
“…The LBP has been used extensively to detect low levels of metabolic endotoxemia associated with obesity [5][6][7][8][9]. LBP has been used to detect varying levels of endotoxemia in inflammatory bowel conditions, pancreatitis, cirrhosis and sepsis where levels in serum can increase 10 to 50 fold during acute inflammation [10,11].…”
Section: Introductionmentioning
confidence: 99%